Is the outcome after lumbar discectomy impacted by fatty infiltration of paraspinal muscles? - Juliana Cardoso Costa Santos (2021)
Study design: Retrospective analisys of prospective collected data study. Objective: To study the prognostic value of paravertebral lumbar muscles atrophy on clinical outcome after lumbar surgery on patients with symptomatic lumbar disc herniation. Summary of Background Data: Cross sectional area (CSA) and fat infiltration (FI) are the best parameters to assess paravertebral muscle atrophy. The role of muscle atrophy in the outcome of patients with symptomatic lumbar disc herniation undergoing surgery remains unclear. Methods: Patients over 18 years old with lumbar disc herniation and radicular pain who underwent single-level discectomy were included. Multifidus, erector spinae and psoas CSA and FI were measured by ImageJ software at the levels of L3-L4, L4-L5 and L5-S1 from T2-weighted MRI axial images. Clinical status was assessed preoperative and one-year postoperative with patient reported outcome measurements (PROMS), that included NRS for back and leg pain, COMI, ODI and EuroQoL-5D. Univariate and multiple linear regression were performed. Results: There where were negative correlations between psoas muscle CSA on the symptomatic side and preoperative PROMS. Erector spinae FI was the only muscle-related factor that correlated to post-surgery PROMS. The relation between erector spinae FI and postoperative COMI was split in three groups: FI < 15%, FI 15-30%, FI > 30%. Postoperative COMI was higher in FI>30% group (median: 4.4, IQR: 3.2) and lower in FI < 15% (median: 1.2, IQR: 1.6) (Kruskal-Wallis, p<0.001). Male gender was associated with better outcome as well as erector spinae FI < 15%, while FI > 30% was related to worse postoperative status. Conclusions: Increased fat infiltration of erector spinae muscles correlates to less favourable clinical outcomes following lumbar discectomies.